The Implementation Of Make A-Match Model In Social Science Learning To Improve Student Learning Outcomes In Class IV SDN 115 Manado - Lompoliuw, B A (Universitas Negeri Manado, 2019)
There is a tendency in the education field today to return to the idea that children will learn better if the environment is created naturally. Learning will be more meaningful if children